Growth Response and Yield of Several Industrial Potato (Solanum tuberosum L.) Varieties in Highland and Medium-Altitude Environments - Budi Setiyono; Irfan Suliansyah; Aprizal Zainal (Journal La Lifesci, 2025)
The potato processing industry in Indonesia continues to face high market demand, while domestic production remains insufficient (reaching only 1.22 million tons in 2023), resulting in dependence on imported raw materials. The expansion of industrial potato cultivation in medium-altitude regions offers considerable potential due to land availability; however, it is constrained by high-temperature stress, requiring varieties that are both tolerant and high yielding. This study aimed to evaluate the growth response and yield performance of three industrial potato varieties Ventury Agrihorti (local), Atlantik (introduced), and Bliss/Chitra (introduced) under two contrasting altitude conditions: medium altitude (600 masl) and high altitude (1500 masl). The experiment employed a Split Plot Design, with observations covering growth parameters, yield components, and tuber quality indicators, including tuber specific gravity (SG). The results revealed a significant interaction between altitude and variety on several parameters, such as plant height, specific leaf weight, number of tubers, and tuber weight per plant. At medium altitude (600 masl), the Atlantik variety demonstrated the best performance, achieving a productivity of 40.39 t/ha with the highest tuber weight. However, Atlantik produced a high proportion of oversize tubers (41.97%), which does not meet industry grading standards. Conversely, at high altitude (1500 masl), Bliss/Chitra showed superior yield performance with a productivity of 42.96 t/ha, followed by Ventury at 38.46 t/ha. Ventury and Bliss/Chitra also excelled in tuber size distribution, producing the majority of tubers (approximately 94–95%) within the Normal category (Ø 4.5–9 cm), which aligns with industrial processing requirements in both altitude conditions. The specific gravity (SG) values of all three varieties ranged from 1.08 to 1.09, indicating compliance with the minimum quality threshold for potato processing industries (>1.08).